PENGKAJIAN PEMUPUKAN FOSFOR (P) DAN KALIUM (K) BERDASARKAN STATUS HARA PADA TANAH DI DAERAH PERTANAMAN JAGUNG DI KABUPATEN PASAMAN BARAT - Yulinar Zubaidah (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2007)
Analysis of phosphorous (P) and potassium (K) fertilization based on soil P and K status at maize planting area in Pasaman Barat regency had done on October until December 2005. The research was conducted by using survey method. The area was surveyed through some trails. Soil samples were taken in every 500 – 1000 m in distance. Global Position System (GPS) was used to determine the coordinates of sampling points. In each point composite bulk soil samples were taken on the top 20 cm soil depth. Each sample represented about 50 ha area. The results showed that from 7702.2 ha area surveyed, there was 5351.5 ha (69.4%) of the area having high P content, 1487.5 Ha (19,3 %) having moderate P, and 863.2 Ha (11,2 %) having low P. Potassium status of the soil in the area was as follows, 2798.4 Ha (36,3 %) having high K, 4499.4 Ha (58,4 %) having moderate K, and 404.4 Ha (5,2 %) having low K. The requirement of SP-36 fertilizer was about 90 kg/Ha, 250 kg/Ha and 500 kg/Ha, for soil having high P, moderate P, and low P content. Potassium was required about 0 kg KCl/Ha, 50 kg KCl/Ha and 250 kg KCl/Ha, for soil having high K, moderate K, and low K, respectively. The both fertilization recommendation was the amount of SP36 and KCl to reach production about 4,5 ton dry weight corn kernel (with water content 14%) or it is equal to 8 ton corn weight during harvesting time (with water content 25%).Key Words: P- soil status, K-soil status, fertilizer recommendation